Objek dan Ruang Lingkup Kajian Hadis Masa Klasik dan Kontemporer - Muhammad Anshori (STAI Darul Kamal NW Kembang Kerang, 2021)
This paper seeks to map and format new typologies in the study of hadith, ranging from the classical period to the present. As the second source or teaching of Islam after the Qur'an, hadith has an important position in the lives of Muslims. From time to time, traditions continue to be studied with a variety of methods and approaches. The hadith which was originally shaped